Electrical Transport Properties of (Bi1.6Pb0.4Sr2Ca2Cu3O10)/Ag Tapes with Different Nanosized MgO. (3rd December 2013) - Yahya, Nabil A. A.; Abd-Shukor, R.
Abstract : MgO nanopowders with average size 20 and 40 nm were introduced into (Bi1.6 Pb0.4 Sr2 Ca2 Cu3 O10 )(MgO) x (x = 0 – 0.15  wt.%) in the pellet form. The optimum amounts for the highest transport critical current density J c were x = 0.10 and 0.01 wt.% for 20 and 40 nm MgO, respectively. These results were used to fabricate MgO added (Bi, Pb)-2223/Ag sheathed tapes using the powder-in-tube method. The tapes were sintered at 845°C for 50 h and 100 h. The structure, microstructure, and J c of the tapes were determined. The temperature and magnetic field dependence of J c for the MgO added tapes exhibited a significant enhancement compared with the nonadded tapes. J c of 20 nm MgO added tape was higher compared with the 40 nm MgO added tape. A higher J c was obtained when the tapes were sintered for 100 h. The increase in J c can be explained as the increase of the flux pinning strength by nanosized MgO. The nanoparticle with size closer to the coherence length was more effective in enhancing J c .